2006
DOI: 10.1063/1.2390671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thin SrTiO3 seed layer to achieve low-temperature crystallization below 300°C and ferroelectricity of lead zirconate titanate thin film

Abstract: The authors report low-temperature preparation of Pb(Zr0.6,Ti0.4)O3 (PZT) thin films below 300°C using SrTiO3 seed layers on (111)Pt∕IrO2∕SiO2∕(001)Si substrates by metal-organic chemical vapor deposition. The critical parameters contributing low-temperature preparation for PZT were crystallinity and orientation of SrTiO3 seeds and deposition rate of PZT films. Using 1–2nm of SrTiO3 with (h00) and (hh0) mixed orientations, polycrystalline PZT films could be obtained at 290°C with deposition rate of 0.5–1.0nm∕m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…However, high-temperature annealing (≥700°C) is regularly required to crystallize the pure BT ferroelectric thin films. Besides, it has been found that the crystallization temperature of ferroelectric films can be reduced by using buffer layer, because the crystallization nucleation of ferroelectric films is much easier on buffer layer than that on the Si or Pt substrate [14][15][16][17] . Besides, it has been found that the crystallization temperature of ferroelectric films can be reduced by using buffer layer, because the crystallization nucleation of ferroelectric films is much easier on buffer layer than that on the Si or Pt substrate [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…However, high-temperature annealing (≥700°C) is regularly required to crystallize the pure BT ferroelectric thin films. Besides, it has been found that the crystallization temperature of ferroelectric films can be reduced by using buffer layer, because the crystallization nucleation of ferroelectric films is much easier on buffer layer than that on the Si or Pt substrate [14][15][16][17] . Besides, it has been found that the crystallization temperature of ferroelectric films can be reduced by using buffer layer, because the crystallization nucleation of ferroelectric films is much easier on buffer layer than that on the Si or Pt substrate [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the XRD analysis results shown in Figure 1, it was believed that the improved crystallinity is related to reducing the leakage current density of BST films. Reduction in the leakage current has been found in PZT films when the films have good crystallinity [17]. In this figure, the sample annealed at 700 • C shows much better leakage current characteristics owing to its better microstructure.…”
Section: Resultsmentioning
confidence: 93%
“…SrTiO 3 (STO) is cubic perovskite structure with lattice parameter of 0.3905 nm, close to that of LNO and of BST. STO has been investigated as a buffer layer [7,9]. In these applications, one takes advantage of its compatible crystal structure with the dielectric material.…”
Section: Introductionmentioning
confidence: 99%